STRATEGI PENGEMBANGAN DESA WISATA HALAL BERBASIS BUMDESA DI JAWA TIMUR; PELUANG DAN TANTANGAN - Dwi Ariady Kusuma; Ridan Muhtadi; Fitriyana Agustin (Ulumuna: Jurnal Studi Keilsman, 2022)
East Java Province is an area that has diversity and uniqueness of regional culture, one of which is found in rural areas which still has the originality and local wisdom of the culture typical of the region. The tourism sector is a mainstay and a source of foreign exchange for the country. The existence of Halal Tourism in Indonesia which can support regional economic development makes East Java a great opportunity to realize a Halal Tourism Village. East Java has 573 Tourism Villages spread across 38 regencies in 2021. However, this opportunity is not matched by optimal management. The presence of Village-Owned Enterprises (BUMDesa) is a solution in developing tourism activities in villages that will drive the community's economy. The purpose of this research is to find out the various kinds of opportunities that exist and the challenges faced by East Java Province in developing Halal Tourism Villages through BUMDesa which is used as a development innovation concept towards better governance. The research method uses descriptive qualitative with primary data from interviews, questionnaires and other sources as a complement. The strategy outlined through the SWOT Matrix approach follows the Internal Factor Analysis (IFAS) and External Factor Analysis (EFAS) indicators. Based on the results of this study, it shows that there is a conceptual framework for Halal Tourism Village in several sectors managed by BUMDesa. Based on the results of the SWOT analysis, it shows several appropriate strategies in developing Halal Tourism Villages such as encouraging domestic and foreign investment in its development, developing a Multi-Platform information center for East Java halal tourism village based on IoT, Establishing an East Java halal tourism management authority and so on. Therefore. The existence of a Halal Tourism Village in East Java has a positive impact on the community. Keywords: Halal Tourism Village, BUMDesa, SWOT, and East Java